Analysis of Children's Errors in Comprehension and Expression. (February 2017) - Hatcher, Ryan C.; Breaux, Kristina C.; Liu, Xiaochen; Bray, Melissa A.; Ottone-Cross, Karen L.; Courville, Troy; Luria, Sarah R.; Langley, Susan Dulong
Children's oral language skills typically begin to develop sooner than their written language skills; however, the four language systems (listening, speaking, reading, and writing) then develop concurrently as integrated strands that influence one another. This research explored relationships between students' errors in language comprehension of passages across oral and written modalities (listening and reading) and in language expression across oral and written modalities (speaking and writing). The data for this study were acquired during the standardization of the Kaufman Test of Educational Achievement–Third Edition (KTEA-3). Correlational analyses from the total sample ( n = 2, 443-3, 552) and within grade bands revealed low to moderate correlations (.26-.50). No evidence of convergent or divergent validity was found when comparing correlations of "same-name" error types (e.g., inferential errors across modalities) with correlations of "different-name" error types. These results support previous research findings and hypotheses that language by ear, eye, hand, and mouth are separable but interacting systems that differ in more ways than modality of input/output.